The Protection of the Rights of the Accused in Syariah Criminal Cases in Malaysia: A Comparative Analysis - Saifuddin, Suhaizad; Mohamadi, Intan Shafinaz (Kanun: Jurnal Undang-undang Malaysia, 2025)
The rights of the accused represent a significant principle in criminal cases. Violations of these rights frequently spark debate and concern. The objective of this study is to analyse the rights of the accused in Syariah criminal cases in Malaysia and compare them with the common law legal system and the Islamic perspective. This study further seeks to identify weaknesses and challenges in the implementation of the rights of the accused within Syariah criminal proceedings in Malaysia, while proposing improvements to ensure more comprehensive and equitable protection. A qualitative approach was employed, with data obtained from primary sources such as legal statutes and reported cases, as well as secondary sources including books and journal articles. The collected data were then analysed through comparative and descriptive analysis methods. The findings of the study indicate that both Islamic law and civil law frameworks provide appropriate protection for the rights of the accused. However, several legal gaps and weaknesses were identified in the current protection mechanisms under Syariah criminal law. Based on these findings, this article suggests that the legal provisions in the Syariah Criminal Procedure Enactment be improved to ensure that the rights of the accused are more comprehensively protected, thus strengthening the administration of Syariah criminal justice in Malaysia. Keywords: Crime, rights of the accused, Syariah law, Common Law, Syariah Criminal Procedure Enactment, Criminal Procedure Code Full text: PDF